Digital Play and Early Learning: Evaluating the Impact of Interactive Educational Technologies on Cognitive and Socio-Emotional Development in Preschoolers - Andi Asrifan; Mark – Jhon R. Prestoza; Akhtem A. Dzhelilov; Sakala Stanley (Universitas Muhammadiyah Mataram, 2026)
The growing incorporation of digital devices into the daily lives of young children has heightened academic discourse around the significance of digital play in early childhood education. Although play-based learning is fundamental to preschool curricula, interactive educational technology is progressively being used to enhance early learning experiences. Nonetheless, empirical evidence on the simultaneous effects of digital play on cognitive and socioemotional development in preschoolers is scarce, particularly in curriculum-aligned classroom settings. This study investigated the effects of structured digital play with interactive educational tools on the development of preschool children. The study employed a quasi-experimental mixed-methods design, involving 72 children aged 4 to 6 years from urban preschools, randomly assigned to experimental and control groups. The results indicated that children in the experimental group showed markedly greater improvements in attention, executive functioning, early literacy and numeracy, and problem-solving skills than those in the control group (Cohen’s d = 0.54–0.68). Moreover, notable improvements were observed in emotional regulation, social interaction, cooperation, and empathy (Cohen’s d = 0.63–0.70). Classroom observations indicated elevated engagement, collaborative behavior, positive emotional expressions, and the essential role of teacher mediation during digital play. The findings indicate that purposefully designed and integrated digital play can serve as a comprehensive pedagogical strategy in early childhood education. The research provides significant insights into early childhood curriculum development, digital teaching methods, and educators' professional growth in technology-integrated learning environments.